Pembangunan Fasilitas Pengolahan Ikan dan Pelatihan Good Manufacturing Practices di Industri Pengolahan Ikan Patin Asap - Dewi Fortuna Ayu; Andarini Diharmi; Evy Rossi; Syahrul Syahrul (Universitas Mathla'ul Anwar Banten, 2021)
CONSTRUCTION OF FISH PROCESSING FACILITIES AND TRAINING OF GOOD MANUFACTURING PRACTICES IN THE SMOKED CATFISH PROCESSING INDUSTRY. This activity aims to increase the production capacity and skills of the workers, which impact the improving quality of smoked catfish products. The activities carried out include the reconstruction of fish processing facilities and training of Good Manufacturing Practices. Results showed that the fish processing facilities that were cleaner, more complete, and ergonomic had reduced weeding time from 8 hours/day to 7 hours/day with the same number of workers. The activities increased production capacity from 800-900 kg to 1-1.2 tons/production (30%). Training activities of Good Manufacturing Practices were also able to increase workers' skills in processing food to SNI 2725: 2013. The training activity was attended by 15 participants, mainly of the workers who implemented health protocols to prevent the transmission of the Covid-19 pandemic. In this activity, the workers were also given some smoked catfish processing equipment and instrumentation.